1997
DOI: 10.1016/s0092-8674(00)80501-2
|View full text |Cite
|
Sign up to set email alerts
|

Apaf-1, a Human Protein Homologous to C. elegans CED-4, Participates in Cytochrome c–Dependent Activation of Caspase-3

Abstract: We report here the purification and cDNA cloning of Apaf-1, a novel 130 kd protein from HeLa cell cytosol that participates in the cytochrome c-dependent activation of caspase-3. The NH2-terminal 85 amino acids of Apaf-1 show 21% identity and 53% similarity to the NH2-terminal prodomain of the Caenorhabditis elegans caspase, CED-3. This is followed by 320 amino acids that show 22% identity and 48% similarity to CED-4, a protein that is believed to initiate apoptosis in C. elegans. The COOH-terminal region of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

49
1,888
1
23

Year Published

1998
1998
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 2,881 publications
(1,961 citation statements)
references
References 43 publications
49
1,888
1
23
Order By: Relevance
“…Whereas other studies have demonstrated that release of cyt c from mitochondria induces a cas-3-mediated apoptotic cascade (Li et al, 1997;Liu et al, 1996;Zou et al, 1997), we asked if heat-shock treatment inhibits cyt cmediated activation of cas-3. As demonstrated previously for other cell types, expression of Hsp27 was induced in 293T cells at 6 ± 8 h after mild heat shock (Figure 1a).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Whereas other studies have demonstrated that release of cyt c from mitochondria induces a cas-3-mediated apoptotic cascade (Li et al, 1997;Liu et al, 1996;Zou et al, 1997), we asked if heat-shock treatment inhibits cyt cmediated activation of cas-3. As demonstrated previously for other cell types, expression of Hsp27 was induced in 293T cells at 6 ± 8 h after mild heat shock (Figure 1a).…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have demonstrated that release of cyt c from mitochondria to cytosol is an important step in inducing cas-3-mediated apoptosis (Li et al, 1997;Liu et al, 1996;Zou et al, 1997). To assess whether Hsp27 functions upstream or downstream to cyt c release from mitochondria, L929/pRc and L929/Hsp27 cells were treated with various agents, such as methylmethane sulphonate (MMS), 1-b-D-arabinofuranosyl-cytosine (ara-C) or staurosporine (STSP), that are known to cause the release of mitochondrial cyt c (Kharbanda et al, 1997a), and cytosols were analysed by immunoblotting (IB) with anti-cyt c. The results demonstrate that MMS treatment of both L929/pRc and L929/Hsp27 cells is associated with the release of cyt c ( Figure 3a, upper panel).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations